Personality traits as risk factors for relapse or recurrence in major depression: a systematic review - Altaweel, Nada; Upthegrove, Rachel; Surtees, Andrew; Durdurak, Buse; Marwaha, Steven (Frontiers in Psychiatry, 2023)
Background: Major depressive disorder (MDD) is highly recurrent. Identifying risk factors for relapse in depression is essential to improve prevention plans and therapeutic outcomes. Personality traits and personality disorders are widely considered to impact outcomes in MDD. We aimed to evaluate the role of personality aspects in the risk of relapse and recurrence in MDD. Method: a PROSPERO-registered systematic review was conducted using Medline, Embase, PsycINFO, Web of Science and CINAHL as data sources, together with hand searching of four journals over the five years till 2022. There was independent abstract selection, quality assessment and data extraction from each study. Results: 22 studies met eligibility criteria involving 12,393 participants. Neurotic personality features are significantly associated with the risk of relapse and recurrence of depression, though the data is not uniform. There is some, though limited, evidence that borderline, obsessive-compulsive and dependent personality traits or disorders increase the risk for relapse in depression. Limitations: The small number, in addition to the methodological heterogeneity of the included studies, did not allow further analysis, such as meta-analysis. Conclusion: People with high neuroticism and dependent personality traits, borderline personality disorder or obsessive-compulsive personality disorder, compared to those without, may be at a higher risk of experiencing relapse or recurrence of MDD. Specific and targeted interventions may potentially reduce relapse and recurrence rates in these groups and could improve outcomes.